The interpretation of dynamic occlusion: Combining contour geometry and accretion/deletion of texture. (October 2022) - Tanrıkulu, Ö. Dağlar; Froyen, Vicky; Feldman, Jacob; Singh, Manish
Abstract: Conventional accounts of motion perception mostly treat accretion/deletion—the appearance or disappearance of texture at a boundary between regions—as an essentially decisive cue to relative depth: the accreting/deleting surface is interpreted as being behind adjacent surfaces. Under certain circumstances, however, accretion/deletion can be perceived in a radically different way: the accreting or deleting surface is seen as rotating in depth in front of adjacent surfaces. This alternative interpretation suggests a problem in conventional accounts of motion interpretation that cannot account for this phenomenon, in part because they ignore the role of contour geometry. In two experiments, we examined the combined role of contour convexity and accretion/deletion in determining the perception of relative depth by parametrically manipulating the strength of each cue. Our results show that convexity plays a more substantial role, often dominating the 3D percept, even in cases when the saliency of the convexity cue is substantially weakened on a contour where the texture was accreting/deleting at high rates. These results highlight the need for a rethinking of theories of perceptual organization in the critical case of moving stimuli.